A chronological review of the development of the shariah supervision system in Islam - Ahmad Faizol, Ismail; Wan Mohd Yusof, Wan Chik (Penerbit Universiti Sultan Zainal Abidin, 2020)
The Shariah supervision system is a process to ensure Shariah compliance in business and economic activities. Nowadays, the Shariah supervision system is structured within the Shariah governance framework. Owing to its development directly from the Islamic financial system, it is somehow presented as if it is new, substantiated by a modern theoretical framework. Less attention has been paid to its background from an Islamic perspective, which, as seen in Islamic historical records, is well connected to many practices. This loophole has to some extent downplayed the significance of the contributions of Islam to this supervision system in the economy. This article offers a review of relevant literature to unearth evidence of the evolution of Shariah supervision from the time of the ancient Islamic world untill now. Using a qualitative research approach, data was collected from Islamic literature relating to the issue, and was analysed thematically. This study found that Shariah supervision is evidently crucial in Islam. It was widely practised by the Prophet Himself, and the superseding caliphs, as a tool to oversee the adherence of business practices in the market to Islamic law. It also evolved following the needs and context of society.